Anonymous
Anonymous asked in Science & MathematicsMathematics · 6 months ago

# √3+√27 How to do Step please Thx?

Update:

Simplify it

Relevance
• 6 months ago

= 4*sqrt(3) =~ 6.928

• 6 months ago

√3 + √27

= √3 + √(9 * 3)

= 1*√3 + 3*√3

= 4√3

• Ian H
Lv 7
6 months ago

√(27) = √(9)*√(3) = 3√(3), so,

√(27) +√(3) = 4√(3)

• 6 months ago

= √3 + √27

= √3 + √(9 * 3)

= √3 + (√9 * √3)

= √3 + (√3² * √3)

= √3 + (3 * √3)

= √3 + 3√3

= 4√3

• 6 months ago

√3 + √27

Simplify the square root of 27, knowing that you can factor a 9 out of it which is a perfect square to get:

√3 + √(9 * 3)

√3 + 3√3

Now you can combine like terms to get:

4√3

• 6 months ago

√3 + √27

= √3 + 3√3

= 4√3

• 6 months ago

First you find the square root of each, THEN you add them.

• David
Lv 7
6 months ago

It is the same as (1 times square root of 3 )+ (3 times the square root of 3) = 4 times square root of 3

The simplest way is to use your calculator.

• TomV
Lv 7
6 months ago

How to do what? What do you want done with the expression?

The expression can be written in a simpler form if you recognize that √3 is a factor of both terms.

√3 + √(3*9)

= √3 + 3√3

= 4√3

• TomV
Lv 7
5 months agoReport

Because √3 + 3√3 = (1)√3 + (3)√3 = (1+3)√3 = 4√3

• J
Lv 7
6 months ago

use √27 = √(9 * 3) = 3√3

• J
Lv 7
6 months agoReport

I was hoping the OP knew that x + 3x = 4x and could instantiate with x= √3